2017
DOI: 10.14310/horm.2002.1727
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of androgen deprivation therapy in patients with prostate cancer: focus on metabolic complications

Abstract: Prostate cancer is the most common cancer among men and androgen deprivation therapy (ADT) is the most effective treatment for this disease. The cornerstone of the treatment of prostate cancer is inhibition of testosterone production which interrupts testosterone-induced growth of the prostate tumor. The dramatic decrease in testosterone levels, however, has several undesirable effects on the metabolic profile and bone metabolism and can also lead to fatigue, loss of libido, gynecomastia, and anemia, provoke v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…CV complications Potential mechanism ADT GnRH antagonist Ischemic heart disease Sarcopenic obesity, lipid profiles (increases in total cholesterol, low-density lipoprotein, highdensity lipoprotein, and triglycerides), reduced insulin sensitivity and diabetes, increased inflammation, atherogenic plaque formation, and plaque destabilization (Scragg et al, 2004;Faris and Smith, 2010;Tzortzis et al, 2017) GnRH agonist Hypertension First-generation antiandrogens Heart failure QTc interval prolongation Atrial fibrillation Second-generation androgen receptor blockers Enzalutamide Ischemic heart disease Delayed rectifier K + current, enhancement of late Na + current, and decrease in NO production in the endothelium (Ikeda et al, 2005;Salem et al, 2019;) Hypertension QTc interval prolongation Darolutamide Ischemic heart disease Unknown Heart failure Apalutamide Ischemic heart disease Unknown Hypertension Androgen metabolism inhibitor Abiraterone acetate Ischemic heart disease Increased mineral corticoid production, reduced androgen synthesis, and fluid retention (Attard et al, 2008) Hypertension Atrial fibrillation QTc interval prolongation Chemotherapy Docetaxel Heart failure Direct cytotoxic effect, oxidative stress, and endothelial dysfunction (Montero et al, 2005;Hung et al, 2015) Left ventricular dysfunction Immunotherapy Pembrolizumab Myocarditis Autoimmune reaction due to T-lymphocytes activation against cardiac tissue cells (Nishimura et al, 2001;Wang et al, 2010;Longoria and Tewari, 2016) Pericarditis Conduction diseases Rhythm disturbances Hypertension Heart failure Ischemic heart disease Sipuleucel-T Hypertension Unknown Cerebrovascular events Notes: ADT, androgen deprivation therapy; GnRH, gonadotropin-releasing hormone; QTc, corrected; QT, interval; LDL, low-density lipoprotein; HDL, high-density lipoprotein; NO, nitric oxide.…”
Section: Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…CV complications Potential mechanism ADT GnRH antagonist Ischemic heart disease Sarcopenic obesity, lipid profiles (increases in total cholesterol, low-density lipoprotein, highdensity lipoprotein, and triglycerides), reduced insulin sensitivity and diabetes, increased inflammation, atherogenic plaque formation, and plaque destabilization (Scragg et al, 2004;Faris and Smith, 2010;Tzortzis et al, 2017) GnRH agonist Hypertension First-generation antiandrogens Heart failure QTc interval prolongation Atrial fibrillation Second-generation androgen receptor blockers Enzalutamide Ischemic heart disease Delayed rectifier K + current, enhancement of late Na + current, and decrease in NO production in the endothelium (Ikeda et al, 2005;Salem et al, 2019;) Hypertension QTc interval prolongation Darolutamide Ischemic heart disease Unknown Heart failure Apalutamide Ischemic heart disease Unknown Hypertension Androgen metabolism inhibitor Abiraterone acetate Ischemic heart disease Increased mineral corticoid production, reduced androgen synthesis, and fluid retention (Attard et al, 2008) Hypertension Atrial fibrillation QTc interval prolongation Chemotherapy Docetaxel Heart failure Direct cytotoxic effect, oxidative stress, and endothelial dysfunction (Montero et al, 2005;Hung et al, 2015) Left ventricular dysfunction Immunotherapy Pembrolizumab Myocarditis Autoimmune reaction due to T-lymphocytes activation against cardiac tissue cells (Nishimura et al, 2001;Wang et al, 2010;Longoria and Tewari, 2016) Pericarditis Conduction diseases Rhythm disturbances Hypertension Heart failure Ischemic heart disease Sipuleucel-T Hypertension Unknown Cerebrovascular events Notes: ADT, androgen deprivation therapy; GnRH, gonadotropin-releasing hormone; QTc, corrected; QT, interval; LDL, low-density lipoprotein; HDL, high-density lipoprotein; NO, nitric oxide.…”
Section: Medicationmentioning
confidence: 99%
“…In humans, it is indicated that androgen suppression may additionally induce or exacerbate CV risk factors through alterations in body composition (sarcopenic obesity), lipid profiles (increases in total cholesterol, lowdensity lipoprotein, high-density lipoprotein, and triglycerides), reduced insulin sensitivity and diabetes (Faris and Smith, 2010). Moreover, ADT may prompt an inflammatory and prothrombotic state that promotes initiation or progression of atherogenic plaque and thus hastens CV system impairment (Tzortzis et al, 2017).…”
Section: Medicationmentioning
confidence: 99%
“…Indeed, studies of individuals with testosterone-dependent malignancies have shown that androgen depletion induces anemia, and leads to loss of lean muscle mass and insulin resistance. 14…”
Section: Research Lettermentioning
confidence: 99%
“…However, ADT is associated with several adverse side effects including osteoporosis, fatigue, depressive symptoms, sexual dysfunction, and metabolic modifications (4). The metabolic changes linked to ADT include altered lipid profile, insulin resistance, increase in adipose tissue, and adipokines (5), which favors a proinflammatory and pro-oxidant environment, giving rise to the so-called metabolic syndrome (6,7), which is a cluster of risk factors for cardiovascular diseases. Indeed, several observational trials have reported an increased risk of cardiovascular diseases in men with PCa on ADT (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%